Synthesis and Fungicidal Screening of 2-Amino-4-(p-bromophenyl)thiazole and Its Metal Complexes - Mishra, A.K.; Lal, Niranjan; Anand, Seema; Kumar, Dushyant (Asian Journal of Chemistry, 2010)
The metal complexes of Mn(II), Ni(II), Co(II), Cu(II), Zn(II) and Fe(III) with 2-amino-4-p-(bromophenyl)thiazole are synthesized and characterized. The structures of the synthesized complexes were established by IR, UV, magnetic moment and elemental analysis. The ligand and the complexes were also screened for their fungicidal activity against different fungi viz., Phoma exigua, Macrophomina phaseoli and Collectotrichum capsici.